A multi-tiered mentoring community approach to research experiences for local students from disadvantaged and underrepresented minority backgrounds - McKean, Thomas; Bates, LaShall; Bates, Gary; Wiersma-Mosley, Jacquelyn D.; Wickramasinghe, S. Ranil (Frontiers in Education, 2024)
Introduction A research and mentoring program was developed to provide local first-generation students, students returning to school after a professional experience, and underrepresented minority students resources and relationships to guide them toward a STEM degree from a four-year university. Methods A multi-tiered mentoring community was formed including direct mentoring from graduate students and faculty advisors, peer mentoring among undergraduate students from different colleges and universities, and high school students to increase the accessibility of research opportunities for this demographic. Local students were recruited from Northwest Arkansas Community College and Upward Bound to combine community college and high school students in a novel manner. The programs were integrated whenever possible to emphasize peer mentoring, including mentoring lunches, research meetings, presentation sessions, conference presentations, and professional development mentoring sessions. Results On the post-program survey, students indicated the community formed in the program supported their STEM identity development, provided them with quality relationships, and developed skills valuable to completion of a STEM degree. This identity development was further evidenced by the students presenting their work at a conference and obtaining additional research positions after the summer program ended. Conclusion The post-program scores and continued efforts of different demographics of students to pursue STEM highlight the versatility of the multi-tiered mentoring community model to serve students from different ages, backgrounds, and demographics.